2018
DOI: 10.1088/2040-8986/aab052
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical optical resonators: fundamental properties and bio-sensing characteristics

Abstract: In this paper, detailed theoretical analysis of cylindrical resonators is demonstrated. As illustrated, these kinds of resonators can be used as optical bio-sensing devices. The proposed structure is analyzed using an analytical method based on Lam's approximation. This method is systematic and has simplified the tedious process of whispering-gallery mode (WGM) wavelength analysis in optical cylindrical biosensors. By this method, analysis of higher radial orders of high angular momentum WGMs has been possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In this scheme of detection, the bio/chemical analytes are directly detected without the laborious process of analyte molecule labeling [ 10 , 11 , 12 ]. Regarding their transducer part, optical biosensors are categorized into different groups of resonator-based [ 13 , 14 , 15 ], waveguide-based [ 16 , 17 ], and interferometric-devices based [ 18 , 19 ]. Although these optical sensors have demonstrated high sensitivities for both bulk and surface sensing measurements [ 20 , 21 , 22 ], they still suffer from a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…In this scheme of detection, the bio/chemical analytes are directly detected without the laborious process of analyte molecule labeling [ 10 , 11 , 12 ]. Regarding their transducer part, optical biosensors are categorized into different groups of resonator-based [ 13 , 14 , 15 ], waveguide-based [ 16 , 17 ], and interferometric-devices based [ 18 , 19 ]. Although these optical sensors have demonstrated high sensitivities for both bulk and surface sensing measurements [ 20 , 21 , 22 ], they still suffer from a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that whispering gallery mode (WGM) resonators like ring resonators can be used as label-free biosensors [10][11][12]. Other geometries of WGM-resonator-based biosensors, like spherical [13,14], cylindrical [15][16][17], and disk structures [18,19], have emerged as alternative device geometries in biosensing. While WGM microsphere and microcylinder biosensors exhibit high quality factors, their circuit integration, mass production and reproducibility are extremely challenging [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our previously published works, we have presented a simple analytical method for modelling of cylindrical resonator based biosensors [16,17]. Here, we use some fast analytical methods to analyze a SOI WGM ring resonator coupled to a straight waveguide.…”
Section: Introductionmentioning
confidence: 99%